2017
DOI: 10.1515/ffp-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of land use change and carbon mapping in the savannah area of Ghana

Abstract: Land-use and land-cover change in both forest reserves and off-reserves is a critical issue in sub Saharan Africa. Deforestation and conversion of forest land to agricultural land continue to be one of the major environmental problems in Africa, and for that matter, Ghana cannot be exceptional; and its resultant effect is the loss in the ecological integrity and the quality of forests, resulting in carbon loss and the resultant climate change effects (FAO 2016). The study area covers the Community Resource Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Grassland ecosystems (i.e., Guinea, Sudan, and Coastal Savannah) which occupy about two thirds of the land area of Ghana [8] are the second most important habitats in Ghana after the high forests-hence their degradation or loss is very significant. However, they are being degraded and lost to anthropogenic activities including, conversion to farmlands using slash and burn clearing practices, expansion of settlements, fuelwood harvesting, bush burning, and overgrazing [9,66,67]. In this study we found that about 51.1% of grassland areas across the country were lost (Figure 5).…”
Section: Changes In Grassland Covermentioning
confidence: 73%
“…Grassland ecosystems (i.e., Guinea, Sudan, and Coastal Savannah) which occupy about two thirds of the land area of Ghana [8] are the second most important habitats in Ghana after the high forests-hence their degradation or loss is very significant. However, they are being degraded and lost to anthropogenic activities including, conversion to farmlands using slash and burn clearing practices, expansion of settlements, fuelwood harvesting, bush burning, and overgrazing [9,66,67]. In this study we found that about 51.1% of grassland areas across the country were lost (Figure 5).…”
Section: Changes In Grassland Covermentioning
confidence: 73%
“…Sullivan et al., 2017). Only studies in Ghana used locally developed biomass equations (Aabeyir et al., 2016; Koranteng et al., 2017). The choice of biomass equation is a crucial step in AGB estimates (Panzou et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to one vegetation type (either forests or savannahs), significantly different estimates have been reported from different locations. For instance, Savannah‐woodland had 5.9 Mg dry biomass/ha in central Burkina Faso, 132.0 Mg dry biomass/ha in southern Ghana but over 170.2 Mg dry biomass/ha in central Ghana (Koranteng, Adu‐Poku, & Zawila‐Niedzwiecki, 2017; Moore et al., 2018; Qasim et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, different scholars have applied useful techniques to study LUCC across Ghana. They primarily focused on changes in and around reserves/catchment areas (Gockowski and Sonwa 2011 ; Alo and Pontius 2008 ), spatial determinants of classes, and dynamisms in future modeling (Addae and Oppelt 2019 ; Koranteng et al 2017a , b ), along with establishing links between demographic changes and land-use systems (Moller-Jensen and Knudsen 2008 ). Other researchers have conducted meta-analysis or review studies on land-use systems and water sedimentation (Boakye et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%